Hydroxypropyl-β-Cyclodextrin Complexes of Styryllactones Enhance the Anti-Tumor Effect in SW1116 Cell Line - Ma, Ru; Chen, Jie-tao; Ji, Xiao-yue; Xu, Xiao-li; Mu, Qing (Frontiers in Pharmacology, 2020)
Styryllactones, a class of compounds obtained from the genus Goniothalamus (Annonaceae), have demonstrated in vitro anti-tumor activity. However, the aqueous solubility of these compounds is poor. In this study, we identified the absolute configurations of the previously isolated compounds, which were first isolated in our laboratory, by single-crystal X-ray diffraction analysis using Cu Kα radiation. Subsequently, the anti-tumor activities of the compounds were evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide staining in four tumor cell lines. The induced apoptosis avtivity of leiocarpin E-7ʹ-Monoacetate was studied by an annexin V fluorescein isothiocyanate/propidium iodide double-staining experiment, and the caspase activity was tested in the SW1116 cell line. The results demonstrated that the anti-tumor activities of cheliensisin A and goniodiol-7-monoacetate were limited by their poor water solubility. To address this issue, hydroxypropyl-β-cyclodextrin (HP-β-CD) complexes of the compounds were synthesized by the saturated aqueous method. The complexes were then analyzed using a differential scanning calorimeter. The IC50 of cheliensisin A was reduced by 45% and 58% against SW1116 and SMMC-7721 cell lines, respectively. Similarly, the IC50 of goniodiol-7-monoacetate was reduced by 55% and 34% against the two tumor cell lines, respectively. To further evaluate whether the styryllactones and complexes possessed selectivity against cancer cell lines and normal cell lines, toxicity against human normal cell line (HEK293T) was evaluated. The results demonstrated that the HP-β-CD complexes displayed more cytotoxicity than the respective pristine compounds against the HEK293T cell line. However, there existed a therapeutic window when the complexes were applied against cancer cell lines. In summary, the synthesis of several styryllactone compounds complexed with HP-β-CD were reported for the first time. These complexes could significantly enhance the cytotoxic effects of styryllactone compounds.